Spontaneous remission of localized myasthenia gravis manifested as megaesophagus in a dog - SOUBASIS (Ν. ΣΟΥΜΠΑΣΗΣ) N.; MYLONAKIS (Μ.Ε. ΜΥΛΩΝΑΚΗΣ) M. E.; PATSIKAS (Μ.Ν. ΠΑΤΣΙΚΑΣ) M. N.; POLIZOPOULOU (Ζ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
A 2.5-year-old male German shepherd-cross dog was admitted for progressively deteriorating regurgitations ofone-month duration. Physical examination was unremarkable, apart from a poor body condition; also, neurological examination did not reveal any abnormality. In thoracic survey radiographs, a generalized esophageal dilation, consistent with megaesophagus, was well visualized. An increased nicotinic acetylcholine receptor antibody titer confirmed the diagnosis of acquired focal myasthenia gravis expressed as megaesophagus in this patient. The only help offered to the dog was a modification of its feeding habits (upright position, small and frequent meals). Within two months of the initial admission and prior to institution of specific treatment for myasthenia gravis, the dog experienced spontaneous and complete clinical remission and remained healthy for the next two years, eating again the normal way, but unfortunately was lost to follow-up. The favourable outcome of megaesophagus due to localized myasthenia gravis is discussed accordingly.